Managing Sustainable Business - Lenssen, Gilbert G.; Smith, N. Craig (Springer, 2019)
This book provides an excellent framework for managers to pursue sustainable business in a strategic way. At the same time, it is a learning model, starting with the foundations of risk management and stakeholder management and moving on to the more complex challenges of strategic differentiation and business model innovation. The most challenging part however is the organizational change management and talent development which needs to follow or go hand in hand with the strategic processes. The wealth of case studies and supporting texts is derived from the legacy of ABIS – The Academy of Business in Society where business schools and companies are working together to enhance the knowledge base for sustainable business. The book follows the rationale of the business manager in a very practical manner, and I hope it will be widely used in executive education and become a core part of learning and talent development.
An Executive Education Case and Textbook